2015
DOI: 10.18632/oncotarget.3222
|View full text |Cite
|
Sign up to set email alerts
|

Loss of β-catenin in adrenocortical cancer cells causes growth inhibition and reversal of epithelial-to-mesenchymal transition

Abstract: Adrenal carcinoma (ACC) is a rare neoplasm with a poor outcome. Aberrant expression of β-catenin has been found in approximatively 30% of ACC. We herein studied its effects on the growth of the human ACC cell line H295R. The cells were infected with short hairpin RNA (shRNA)-mediated silencing β-catenin. Two shRNAs used induced down-regulation of β-catenin protein levels. The expression of these shRNAs decreased cell growth and increased H295R cells in S and G2/M phases. This cytostatic effect is due to a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Our findings support those of Salomon et al [39], where siRNAs were used to silence beta-catenin expression in H295R. They found that silencing beta-catenin decreased cell growth, decreased migration and invasion, increased cell apoptosis, and induced cell cycle S/G2 arrest.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support those of Salomon et al [39], where siRNAs were used to silence beta-catenin expression in H295R. They found that silencing beta-catenin decreased cell growth, decreased migration and invasion, increased cell apoptosis, and induced cell cycle S/G2 arrest.…”
Section: Discussionsupporting
confidence: 92%
“…Mutations in β-catenin have been associated with poor prognosis in patients with ACC, and higher-grade ACC is associated with higher β-catenin expression (25). Silencing of β-catenin in NCI-H295R has been shown to decrease proliferation, induce cell cycle arrest and apoptosis, reverse the EMT phenotype, and inhibit in vivo tumor development (26, 27). These findings suggest that the WNT/β-catenin pathway plays a major role in ACC tumorigenesis and may be an effective therapeutic target for ACC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…H295R human ACC cells harbor an activating β-catenin mutation. Knockdown of β-catenin in these cells causes cell cycle arrest and increased cell death in vitro , and complete tumor regression in vivo (Gaujoux et al, 2013; Salomon et al, 2015). Small molecule antagonism of the TCF/β-catenin complex also results in H295R growth inhibition (Doghman et al, 2008).…”
Section: Wnt/β-catenin Signalingmentioning
confidence: 99%